Japanese painting - Lésoualc’h, Théo (Heron, 1970)
This book consists of the following many parts: Japanese painting, evidence and documents, the schools of Japanese painting, school and painters, chronology, periods of Japanese and neighbouring civilisations, periods of Japanese painting and the four major periods, museums, maps, ...